2017
DOI: 10.1186/s12913-017-2586-4
|View full text |Cite
|
Sign up to set email alerts
|

An Australian general practice based strategy to improve chronic disease prevention, and its impact on patient reported outcomes: evaluation of the preventive evidence into practice cluster randomised controlled trial

Abstract: BackgroundImplementing evidence-based chronic disease prevention with a practice-wide population is challenging in primary care.MethodsPEP Intervention practices received education, clinical audit and feedback and practice facilitation.Patients (40‑69 years) without chronic disease from trial and control practices were invited to participate in baseline and 12 month follow up questionnaires.Patient-recalled receipt of GP services and referral, and the proportion of patients at risk were compared over time and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(19 citation statements)
references
References 37 publications
0
13
0
Order By: Relevance
“…social cognitive theory [19], the transtheoretical model of change [24], or self-affirmation on health-behavior change [25] may be beneficial in understanding resistance towards beneficial health information and in reducing it. The essential goal is to implement functioning theory-based health promotion in everyday primary care actions [11]. However, the current health promotion strategies do not seem to be beneficial in practice.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…social cognitive theory [19], the transtheoretical model of change [24], or self-affirmation on health-behavior change [25] may be beneficial in understanding resistance towards beneficial health information and in reducing it. The essential goal is to implement functioning theory-based health promotion in everyday primary care actions [11]. However, the current health promotion strategies do not seem to be beneficial in practice.…”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested that in order to be more effective, health promotion should be more personalized and adapted more to individual characteristics and readiness for health behavior change [8]. Because of the complexity in the health behavior of the population, there is an evident need for individual assessment and goal setting, educating and training, and following up on the subjects to whom the lifestyle interventions are targeted [11]. The epidemiological evidence or medical knowledge oriented toward risks and dangers alone may not be efficient in health promotion.…”
Section: Introductionmentioning
confidence: 99%
“…All studies except one, 15 which did not show follow-up data, reported data loss. Thirteen studies used an intention-to-treat analysis; 17 , 19 , 21 , 24 , 26 28 , 30 , 31 , 34 , 35 , 37 , 38 the other studies did not report how they approached the missing data in the analyses. Further bias might have been introduced in 18 studies either by not reporting fidelity data, or through low fidelity to the intervention.…”
Section: Resultsmentioning
confidence: 99%
“…In nine studies, the intervention was delivered by primary care physicians, 15 , 17 19 , 24 , 32 , 33 , 36 , 38 in 10 by practice nurses, 20 22 , 25 29 , 30 , 34 and in five by both. 16 , 23 , 31 , 35 , 37 Fourteen studies evaluated a PA intervention 16 19 , 23 , 25 , 27 29 , 31 , 33 36 and 10 a lifestyle intervention. 15 , 20 , 21 , 22 , 24 , 26 , 30 , 32 , 37 , 38 Three studies included a single behaviour change consultation as intervention, 16 18 and 10 studies a baseline behaviour change consultation with follow-up visits or phone call.…”
Section: Resultsmentioning
confidence: 99%
“…To date, it remains unclear how effective audits and feedback are at improving clinical practice, and which characteristics of audits and feedback have the greatest impact [23,24]. Several studies conducted in the primary care setting have attempted to determine the effects of audit and feedback interventions in cardiovascular health [25,26,27,28,29,30,31]. In an article that evaluated the effects of audit and feedback on secondary prevention in patients with non-acute stroke, blood pressure and metabolic control were considered adequate in 73% of patients with hypertension and 62% of patients with diabetes, respectively [25].…”
Section: Introductionmentioning
confidence: 99%